O IZIDU POSTHUMNE PESNIŠKE ZBIRKE ERICHA PRUNČA: Erich Prunč: Tihožitja in Besi. Celovec: Mohorjeva družba, 2019. - Čeh Steger, Jožica (Slavia Centralis, 2020)
The author of the article presents the posthumous edition of the collection Tihožitja in Besi (2019) by the Slavic scholar and linguist Erich Prunč.
Keywords: Tihožitja in Besi; Erich Prunč; collection of poems; review; linguistics; poetry